Autophagy proteins control goblet cell function by potentiating reactive oxygen species production - Patel, Khushbu K (European Molecular Biology Organization, 2013)
Delivery of granule contents to epithelial surfaces by secretory cells is a critical physiologic process. In the intestine, goblet cells secrete mucus that is required for homeostasis. Autophagy proteins are required for secretion in some cases, though the mechanism and cell biological basis for this requirement remain unknown. We found that in colonic goblet cells, proteins involved in initiation and elongation of autophagosomes were required for efficient mucus secretion. The autophagy protein LC3 localized to intracellular multi-vesicular vacuoles that were consistent with a fusion of autophagosomes and endosomes. Using cultured intestinal epithelial cells, we found that NADPH oxidases localized to and enhanced the formation of these LC3-positive vacuoles. Both autophagy proteins and endosome formation were required for maximal production of reactive oxygen species (ROS) derived from NADPH oxidases. Importantly, generation of ROS was critical to control mucin granule accumulation in colonic goblet cells. Thus, autophagy proteins can control secretory function through ROS, which is in part generated by LC3-positive vacuole-associated NADPH oxidases. These findings provide a novel mechanism by which autophagy proteins can control secretion.